TWEAK Promotes the Proliferation of Squamous Cell Carcinoma Cells Through Activating cIAP1 Signals - Liang, Lili; Cheng, Chuantao; Hu, Guanglei; Wang, Xuening; Liu, Jing; Yan, Zhu; Zeng, Weihui; Xia, Yumin (Frontiers in Oncology, 2020)
It has recently been shown that tumor necrosis factor (TNF)-like weak inducer of apoptosis (TWEAK) induces the proliferation of squamous cell carcinoma (SCC) cells, but the underlying mechanism is unknown. This study was designed to elucidate the role of cellular inhibitor of apoptosis 1 (cIAP1) in TWEAK-induced proliferation of SCC cells. Human SCC cells (SCC-13) were cultured in vitro and stimulated with TWEAK or TNF-related apoptosis-inducing ligand (TRAIL). We found that TWEAK induced cytoplasmic cIAP1 expression and ubiquitination of RIP1 in cells, followed by the activation of canonical nuclear factor kappa B signals. The CIAP1 inhibitor MV1 abrogated TWEAK-induced proliferation of SCC-13 cells. Moreover, the interaction between TWEAK and its receptor, fibroblast growth factor-inducible 14 (Fn14), enhanced the expression of TRAIL receptor types 3 and 4 (TRAIL-R3/4). Furthermore, transfection of TRAIL-R3/4 siRNA blocked the promotion of proliferation and cIAP1 expression by TWEAK on SCC-13 cells. Therefore, interaction of TWEAK with Fn14 induces the proliferation of SCC cells by activating cIAP1 signals. Targeting the downstream cIAP1 signals may attenuate the effect of TWEAK on SCC cells.